Long-Term Remission Achieved by Ponatinib and Donor Lymphocytes Infusion in a Ph+ Acute Lymphoblastic Leukemia Patient in Molecular Relapse After Allogenic Stem Cell Transplant and Dasatinib: A Case Report - Botta, Cirino; Caruso, Nadia; Bossio, Sabrina; Storino, Francesca; Console, Giuseppe; Martino, Massimo; Mendicino, Francesco; Lucia, Eugenio; Morelli, Rosellina; Correale, Pierpaolo; Morabito, Fortunato; Gentile, Massimo; et al. (Frontiers in Oncology, 2020)
Currently, the prognosis of Ph+ acute lymphoblastic leukemia (Ph+ ALL) patients relapsing after an allogenic hematopoietic stem cell transplantation (allo-SCT) remains poor, with few therapeutic options available. Here we present the case of a 32 years old patient with dasatinib-resistant post-transplant molecular relapse of ALL, who received, as second-line therapy, the combination of ponatinib and donor lymphocyte infusion (DLI). The therapy was safe and the patient achieved a sustained minimal residual disease negative disease, still ongoing after 22 months, which was accompanied by several changes in the immune populations distribution within the bone marrow (i.e.: the increase in the CD8/CD4 lymphocytes ratio). Our report provides evidence of the efficacy of the third generation TKI inhibitor ponatinib in combination with DLI as second line therapy for Ph+ ALL relapsing after an allo-SCT.